2008
DOI: 10.1016/j.bbrc.2008.01.085
|View full text |Cite
|
Sign up to set email alerts
|

Solution NMR studies provide structural basis for endotoxin pattern recognition by the innate immune receptor CD14

Abstract: CD14 functions as a key pattern recognition receptor for a diverse array of gram-negative and grampositive cell-wall components in the host innate immune response by binding to pathogen-associated molecular patterns (PAMPs) at partially overlapping binding site(s). To determine the potential contribution of CD14 residues in this pattern recognition, we have examined using solution NMR spectroscopy the binding of three different endotoxin ligands, Lipopolysaccharide, lipoteichoic acid and a PGN-derived compound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…2A and 2B). Similar to MD-2, previous circular dichroism, tryptophan fluorescence, and NMR studies suggest that LPS binding does not induce large structural changes in human CD14 (50, 80). Given these volume constraints and pocket rigidity, it is unlikely that CD14 can accommodate all the acyl chains of LPS.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…2A and 2B). Similar to MD-2, previous circular dichroism, tryptophan fluorescence, and NMR studies suggest that LPS binding does not induce large structural changes in human CD14 (50, 80). Given these volume constraints and pocket rigidity, it is unlikely that CD14 can accommodate all the acyl chains of LPS.…”
Section: Discussionsupporting
confidence: 60%
“…For example, previous work has shown that mutation of E47, which falls near the front of the rim in α1, to either lysine or arginine can block binding of P. gingivalis LPS (85). Solution NMR spectroscopy analyzing soluble CD14 aa 20-171 bound to the Re chemotype of LPS did not have structural assignments available upon publication, but does show high average temperature factor evidence for hydrophilic residues at the rim suggesting local flexibility to accommodate LPS binding (50). Further work to develop a ligand bound CD14 structure would help to clarify the roles of both the hydrophobic binding pocket and the hydrophilic rim residues required for ligand binding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, as they block CD14 function, it is likely that they bind to either the N-terminal LPS-binding pocket of CD14 or parts of the LPS-signaling motif. Importantly, the hydrophobic binding pocket can also accommodate other acylated endogenous and exogenous ligands of CD14 and TLRs (49)(50)(51). Therefore anti-CD14 Abs, like r18D11 and rMil2, may affect pattern recognition signaling upon a wide range of threats, being more efficient than, for example, LPS mimics.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, other serum molecules, such as LBP, play a role by extracting LPS from the bacterial cell wall, disrupting LPS aggregates through recognition of the lipid component of LPS, and enhancing binding of LPS to sCD14 and mCD14 [4 -6]. Furthermore, other lipid-based TLR agonists, such as the TLR2 agonists lipoteichoic acid and triacylated and diacylated lipopeptides, also use LBP and CD14 in a similar manner to LPS [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%